2010
DOI: 10.1016/j.futures.2009.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Non-receptive organizational contexts and scenario planning interventions: A demonstration of inertia in the strategic decision-making of a CEO, despite strong pressure for a change

Abstract: Publisher's copyright statement:Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…The scenarios were also presented periodically to the Committee of Managing Directors, at ''high-level business-and regional-specific meeting,'' and internal approval was then required from the Chairman of Shell prior to presenting the scenarios to a group of 300 Shell leaders [28]. These high-level, powerful audiences would likely have had an impact on how scenarios were developed and presented due to organizational politics and possible bias resulting from stakeholder interests [29]. Therefore, it seems unlikely that complete unrestrainedness would be possible in this type of top-down, consensusoriented environment.…”
Section: Variationmentioning
confidence: 99%
See 2 more Smart Citations
“…The scenarios were also presented periodically to the Committee of Managing Directors, at ''high-level business-and regional-specific meeting,'' and internal approval was then required from the Chairman of Shell prior to presenting the scenarios to a group of 300 Shell leaders [28]. These high-level, powerful audiences would likely have had an impact on how scenarios were developed and presented due to organizational politics and possible bias resulting from stakeholder interests [29]. Therefore, it seems unlikely that complete unrestrainedness would be possible in this type of top-down, consensusoriented environment.…”
Section: Variationmentioning
confidence: 99%
“…O'Keefe and Wright's [29] case study on an engine manufacturing organization's attempt to employ scenario planning demonstrated how bias and resistance from stakeholders, in this case the CEO and a few top managers, could prejudice or even derail the objectives of scenario planning. In this case, despite organization-wide consensus that change was necessary in order for the company to survive its attempted expansion, a segment of key stakeholders dropped out of the scenario planning exercise midway through due to their desire to control the strategic course of the organization, which reinforced structural inertia.…”
Section: Inertiamentioning
confidence: 99%
See 1 more Smart Citation
“…However, as Diamond [21] demonstrates, historical analysis indicates that human practice is always culturally and historically determined. Without sufficient reflection, a practical response can be reactive rather than proactive [49]. Such an insight should strike a note of caution for all of us looking for ways to respond to climate change.…”
Section: Practical Lessons 1: Multi-temporal Open Ended Systems Thimentioning
confidence: 99%
“…The present simply seems too dominant, too real, for any considerations about an open-ended future to be relevant. Such 'strategic inertia' [49] is a real barrier to effective action in the area of climate change. Historical reflection and the scenarios distilled from this analysis offer powerful evidence that longer-term thinking is very much to the advantage of those locked in a struggle to ensure viable and sustainable social and economic structures into the future [87].…”
Section: Practical Lesson 4: Probable Possible and Preferable Futuresmentioning
confidence: 99%